Supraspinal Mechanisms of Pain and Nociception - Michael Hauck; Jürgen Lorenz (2018)
This exhaustively comprehensive edition of the classic Bonica’s Management of Pain , first published 65 years ago, expertly combines the scientific underpinnings of pain with clinical management. Completely revised, it discusses a wide variety of pain conditions—including neuropathic pain, pain due to cancer, and acute pain situations—for adults as well as children. An international group of the foremost experts provides comprehensive, current, clinically oriented coverage of the entire field. The contributors describe contemporary clinical practice and summarize the evidence that guides clinical practice. Substantially updated with theoretical advancements and contemporary therapies that have emerged since the previous edition published over a decade ago. Broad authorship by researchers and practitioners from the many disciplines that participate in pain medicine, including anesthesiology, neurology, physical medicine and rehabilitation, palliative care, psychology, social sciences, and more. Addresses the economic, political, legal, ethical, and sociological considerations of pain; evaluation of the pain patient; pain conditions; methods for symptomatic control; and provision of pain treatment. Packed with hundreds of full-color illustrations and tables. Enhance Your eBook Reading Experience Read directly on your preferred device(s), such as computer, tablet, or smartphone. Easily convert to audiobook, powering your content with natural language text-to-speech.